Potassium Carbonate Promoted Nucleophilic Addition of Alkenes with Phosphites - Huang, Zhenjun; Liu, Wei; Li, Sen; Yang, Yutian; Guo, Shengmei; Cai, Hu (Synlett, 2020)
A facile hydrophosphonylation of alkenes by phosphites promoted by potassium carbonate was developed. The reaction features include easy handling, environmental friendliness, and avoidance of the use of strong bases. A variety of alkenes are tolerated in this reaction, with moderate to excellent yields.
Keywords: potassium carbonate; addition; alkenes; phosphites; hydrophosphonylation